Autoria em hipermídia: o modelo OOHDM aplicado ao ensino de linguagens de programação - Cunha, Maria Carolina Ribeiro Martins da (2002)
This work describes a hypermidia application’s process of modeling and implementing for programing language learning. The main concepts related to the hypermidia are presented. The application’s modeling was done using the OOHDM – “Object Oriented Hypermidia Design Model”. An exemple of implementation was built with the software Toolbook. It was concluded thah the model OOHDM, independently of the implementation’s process, was able to structure complex applications, facilitating the maintenance and giving support to the reuse.